2012
DOI: 10.1515/ling-2012-0023
|View full text |Cite
|
Sign up to set email alerts
|

/r/-sandhi in early 20th century New Zealand English

Abstract: Most work on linking and intrusive /r/ is conducted within the context of theoretical model building. This paper contributes some empirical data on the phenomenon by conducting the first large-scale acoustic analysis on the production of linking and intrusive /r/ in spontaneous speech. We analyze linking and intrusive /r/ in the speech of New Zealanders born between 1900 and 1935 -a period during which New Zealand English had recently become reliably nonrhotic, and the system of linking and intrusive /r/ was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 18 publications
5
30
1
Order By: Relevance
“…Pairwise comparisons showed, in support of Hay & Maclagan (2012), that the low frequency users had significantly higher F3 than the middle (p < .0001) and high frequency users (p < .0001). The middle and high frequency users also differed significantly from each other on F3 (p < .01).…”
Section: Acoustic Analysismentioning
confidence: 60%
See 1 more Smart Citation
“…Pairwise comparisons showed, in support of Hay & Maclagan (2012), that the low frequency users had significantly higher F3 than the middle (p < .0001) and high frequency users (p < .0001). The middle and high frequency users also differed significantly from each other on F3 (p < .01).…”
Section: Acoustic Analysismentioning
confidence: 60%
“…In contrast, Hay & Maclagan (2012) and Hay & Sudbury (2005) show that female speakers of NZE used linking 'r' significantly less frequently than males.…”
Section: Change In Progressmentioning
confidence: 71%
“…Words that often occur before vowels, then, will have had a greater chance of being experienced more often with /ɹ/ than words that occur more often before consonants. Hay and Maclagan () show the role that this increased experience plays: Words that occur more often before vowels are more likely to be produced with an /ɹ/ in the relevant environment. A further case of a word's distribution of realizations impacting individual tokens is reported by Sóskuthy, Foulkes, Haddican, Hay, and Hughes () and Sóskuthy, Foulkes, Haddican, and Hughes (this volume).…”
Section: Context Of Use Shapes Word Representationsmentioning
confidence: 99%
“…At the lexical level, a number of studies have demonstrated word-specific pronunciation generalizations (see e.g. Pierrehumbert 2002;Hay and Maclagan 2012) For example, the length of the penultimate vowel in the word memory shows a wide range of variation [mɛməri ~ mɛmri] that is not found in the minimally distinct word mammary [maeməri ~ *maemri]. Word-specific generalizations such as this cannot be easily accommodated within a strict hierarchy of nested abstractions, where only the smallest unit makes contact with phonetic detail.…”
Section: Components Of the Network Feedback Model 21 Levels Of Organmentioning
confidence: 99%